The Role of Digital Tools in Enhancing Collaborative Learning in Secondary Education - Elsa Oskarita; Hadid Nur'afra Arasy (International Journal of Educational Research, 2024)
This study investigates the impact of digital tools on collaborative learning among secondary school students. By analyzing various online platforms and educational apps, we examine how these tools foster teamwork, communication, and problem-solving skills. Data were collected from a sample of 300 students across five schools, using surveys and focus groups. Results show that students who used digital tools for collaboration demonstrated significant improvements in engagement, critical thinking, and peer interaction. The study concludes that integrating digital tools into classroom activities can enhance the effectiveness of collaborative learning.